Offshoring of Services and Corruption: Do Firms Escape Corrupt Countries? - Patrik Karpaty; Patrik Gustavsson Tingvall (Örebro University School of Business, 2012)
In this paper, we analyze how the offshoring of services by Swedish firms is affected by corruption in target economies. The results suggest that firms avoid corrupt countries and that corruption reduces the amount of offshored services. In addition, the sensitivity to corruption is highest for poor countries, and large and internationalized firms are the ones that tend to be the most sensitive to corruption.
Keywords: C23; D22; F23; L24; 330; Corruption; Services; Offshoring; Gravity model; Firm level data